Alginate sulfate-based hydrogel/nanofiber composite scaffold with controlled Kartogenin delivery for tissue engineering. (15th August 2021) - Zare, Pariya; Pezeshki-Modaress, Mohamad; Davachi, Seyed Mohammad; Zare, Pouria; Yazdian, Fatemeh; Simorgh, Sara; Ghanbari, Hadi; Rashedi, Hamid; Bagher, Zohreh
Abstract: In this study, we fabricated two different arrangements of laminated composite scaffolds based on Alginate:Alginate sulfate hydrogel, PCL:Gelatin electrospun mat, and Kartogenin-PLGA nanoparticles (KGN-NPs). The optimized composite scaffold revealed a range of advantages such as improved mechanical features as well as less potential of damage (less dissipated energy), interconnected pores of hydrogel and fiber with adequate pore size, excellent swelling ratio, and controlled biodegradability. Furthermore, the synthesized KGN-NPs with spherical morphology were incorporated into the composite scaffold and exhibited a linear and sustained release of KGN within 30 days with desirable initial burst reduction (12% vs. 20%). Additionally, the cytotoxicity impact of the composite was evaluated. Resazurin assay and Live/Dead staining revealed that the optimized composite scaffold has no cytotoxic effect and could improve cell growth. Overall, according to the enhanced mechanical features, suitable environment for cellular growth, and sustained drug release, the optimized scaffold would be a good candidate for tissue regeneration. Highlights: Laminated hydrogel/fiber composite release systems were mechanically optimized. The composite scaffold is based on Alg hydrogel, PCL:G fibers, and KGN-PLGA nanoparticles. Sustained KGN release achieved by incorporating KGN-PLGA nanoparticles into the composite scaffold. In-vitro analysis confirmed the biocompatibility of the composite scaffolds. The optimized composite scaffold can be a suitable candidate in tissue engineering.